2008
DOI: 10.1039/b701676j
|View full text |Cite
|
Sign up to set email alerts
|

The human oxygen sensing machinery and its manipulation

Abstract: Animals respond to the challenge of limited oxygen availability by a coordinated response that works to increase oxygen supply and minimize tissue damage. The chronic hypoxic response is mediated by the alpha,beta-hypoxia inducible transcription factor (HIF) that enables the expression of a gene array. Because this array includes genes encoding for proteins that regulate processes including red blood cell and blood vessel formation, manipulation of the HIF system has potential for the treatment of ischemic dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
88
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(90 citation statements)
references
References 59 publications
1
88
0
1
Order By: Relevance
“…The inactive analog D-NAME had no effect, ruling out the possibility that L-NAME is acting through some nonspecific mechanism. This suggests that the initial burst of superoxide caused by 20-HETE is generated by NOS, presumably by NOS uncoupling, as suggested by Cheng et al (12). Our results indicate that rapid superoxide generation induced by 20-HETE via NOS triggers a series of biochemical events, which are reflected in the changes in VEGF, NADPH oxidase activation, and HIF-1␣ upregulation.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…The inactive analog D-NAME had no effect, ruling out the possibility that L-NAME is acting through some nonspecific mechanism. This suggests that the initial burst of superoxide caused by 20-HETE is generated by NOS, presumably by NOS uncoupling, as suggested by Cheng et al (12). Our results indicate that rapid superoxide generation induced by 20-HETE via NOS triggers a series of biochemical events, which are reflected in the changes in VEGF, NADPH oxidase activation, and HIF-1␣ upregulation.…”
Section: Discussionsupporting
confidence: 79%
“…In separate experiments, we confirmed that stimulation with exogenous VEGF leads to HIF-1␣ upregulation in the ECs that we used. Among the genes regulated by HIF, VEGF is one of the most important regulator of neovascularization responses by ECs and EC survival (12,18,19,29). The 20-HETE induction of HIF-1␣ expression requires the prior increases in VEGF synthesis and release.…”
Section: Discussionmentioning
confidence: 99%
“…Under normoxic conditions, the HIF-1␣ subunit is synthesized and subjected to hydroxylation on proline residue 402 and/or 564 by prolyl hydroxylase domain (PHD) proteins (principally PHD2) that use O 2 and ␣-ketoglutarate as substrates (FIGURE 1A) to catalyze a dioxygenase reaction in which one oxygen atom is inserted into the proline residue and the other oxygen atom is inserted into ␣-ketoglutarate to form succinate and CO 2 (12,30). The protein OS-9 binds to both PHD2 and HIF-1␣, thereby facilitating hydroxylation (4).…”
Section: Continuous Hypoxiamentioning
confidence: 99%
“…Plant P4Hs have a ϳ30% sequence identity to the catalytic domain of the C-P4H ␣-subunits (11,12), and they also resemble C-P4Hs in that they hydroxylate proline-rich polypeptides and are located in the lumen of the endoplasmic reticulum (2). HIF-P4Hs, on the other hand, are cytoplasmic and nuclear enzymes (8,9) that act on proline residues in -Leu-X-X-Leu-Ala-Pro-motifs in HIF-␣ (13,14). C-P4Hs hydroxylate the central proline of the -X-Pro-Gly-repeats of collagen polypeptides, typically generating about 100 4Hyp residues in polypeptides with a length of about 1000 amino acids.…”
Section: R-hydroxyproline (4hyp)mentioning
confidence: 99%